A review on integrated vermifiltration as a sustainable treatment method for wastewater. (15th February 2023) - Das, Pragyan; Paul, KakoliKarar
Abstract: To overcome the scarcity of fresh water, concerned authorities worldwide are bound to think about remediation and reuse of domestic and industrial effluents. The present review study on integrated vermifiltrationwith hydroponic system explains mechanism followed in system and presently the reutilization and remediation of domestic and industrial effluents. It explains the result of integrated vermifiltration and recognizes factors such as clogging, hydraulic loading rate or rain on bed, salinity, and sunlight affect the efficiency of system. The study also focuses on limitations associated with vermifiltration and also suggestions have been made for enhancing the sustainability and performance of existing practices. After literature review, integrated vermifiltration with hydroponic system considered as a natural and eco-friendly method for treating polluted water. Active zone of vermifilter remove organics, nitrate from nitrogen, total and dissolved phosphorus from wastewater. The vermifiltration and integrated vermifiltration with macrophyte able remove chemical oxygen demand (COD) in the range (53.7%–64.4%) and (75.5%–82.8%) respectively. The integrated system reduces land consumption and wastewater can be reutilized in cultivation. Highlights: Mechanism behind integrated vermifiltration has been discussed. Limitation and benefit of the system is identified. Future research prospective has been identified and explained. Integrated vermifiltation with hydroponic plants are able to degrade waste. Reutilization of treated wastewater has also been identified.